Sorption behavior and preliminary pervaporation results of cross-linked polyvinylalcohol and polydimethylsiloxane membranes prepared for the separation of water-ethylacetate mixtures - Salt, Y; Hasanoglu, A; Dinçer, S (TAYLOR & FRANCIS INC, 2003)
Since pervaporation process is the coupling of solution and diffusion mechanisms, a sorption study was carried out with membranes prepared by cross-linking polyvinylalcohol (PVA) and polidimethylsiloxane (PDMS). Tartaric acid (Tac) was used as the cross-linking agent for PVA, and a commercial cross-linking agent was used for PDMS. Sorption experiments were carried out at 30-50degreesC temperature range in pure water and ethyl acetate using the films prepared. The PVA and PDMS films prepared preferentially sorb water and ethylacetate, respectively. A pervaporation study at 30degreesC was carried out for pure ethylacetate and pure water, and mixtures of ethylacetate containing 2 and 2.5 wt% water using 100 mum thick PVA membrane. The results indicate that the PVA membrane prepared is extremely selective for water.
Keywords: pervaporation; sorption; tartaric acid; polyvinylalcohol; polydimethylsiloxane; ETHYL-ACETATE; ORGANICS; Engineering